Creep damage analysis of simulated-HAZ notched bar specimens of modified 9Cr-1Mo steel - Takashi HONDA (The Japan Society of Mechanical Engineers, 2017)
From the standpoint of evaluating Type IV creep damage in the fine-grained heat affected zones (FGHAZ) of welded joints, an analysis method combining continuum damage mechanics (CDM) and a cavity nucleation model is proposed and applied to the creep testing of simulated-FGHAZ notched bars of mod. 9Cr-1Mo steel at 650°C. The Perrin-Hayhurst CDM model is adopted, which considers both softening by precipitate coarsening and damage by creep cavities. For the cavity nucleation model, a proposal by Gonzalez and Cocks is employed, which considers the randomness of grain-boundary-facet orientations in a polycrystalline material and gives a nucleation rate that is a function of the creep strain rate and a tri-axiality factor. The critical value of the damage parameter, corresponding to the initiation of micro cracks due to the coalescence of creep cavities, is expressed in terms of a critical value of the number density of creep cavities as determined from grain-boundary-resistance model simulations by the present authors. Creep rupture experiments have been conducted for circumferentially notched bar specimens with two kinds of notch acuities. The applicability of the combined CDM and cavity nucleation model is demonstrated by comparing the distribution of creep cavities observed experimentally with the simulation results. The final rupture life of the circumferentially notched bar specimens was also predicted to within a factor of two.